Polarizing plate with a phase difference layer
The polarizing plate with a retardation layer addresses the issue of uneven reflected light in display devices by using a layered structure with specific refractive indices and thicknesses, resulting in improved visibility.
Patent Information
- Application Number
- JP2023023083
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-02-17
- Publication Date
- 2025-04-21
- Estimated Expiration
- 2036-07-29
AI Technical Summary
Display devices using circular polarizers suffer from unevenness in reflected light, leading to insufficient visibility.
A polarizing plate with a retardation layer is designed, comprising a polarizer, a first retardation layer, and a second retardation layer, bonded together with specific adhesive layers, where the retardation layers have thicknesses of 5 μm or less and refractive indices between 1.50 and 1.70.
This configuration effectively suppresses unevenness in reflected light, thereby enhancing visibility in display devices.
Smart Images

Figure 0007665666000002 
Figure 0007665666000001
Abstract
Description
[Technical Field]
[0001] The present invention relates to a polarizing plate with a retardation layer. [Background technology]
[0002] Display devices are known that have a circular polarizer disposed on the viewing side of the display panel to improve visibility problems caused by reflection of external light and glare of the background on the display screen of the display device. Patent Documents 1 and 2 propose a polarizer that reduces reflection of incident light from an oblique direction during black display and achieves excellent reflective hues in oblique directions, and a display device equipped with the polarizer. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Laid-Open No. 2015-111236 [Patent Document 2] Japanese Patent Application Laid-Open No. 2015-210459 Summary of the Invention [Problem to be solved by the invention]
[0004] However, the display devices using the polarizing plates described in Patent Documents 1 and 2 have the problem that the reflected light is uneven and visibility is insufficient.
[0005] The present invention has been made in view of the above-mentioned problems, and an object of the present invention is to provide a polarizing plate with a retardation layer that can suppress unevenness in reflected light and improve visibility. [Means for solving the problem]
[0006] The retardation layer-attached polarizing plate of the present invention includes a polarizer, a first retardation layer, and a second retardation layer in this order, the polarizer and the first retardation layer are bonded together via a first adhesive layer, and the first retardation layer and the second retardation layer are bonded together via a second adhesive layer, the thicknesses of the first retardation layer and the second retardation layer are 5 μm or less, the average refractive indexes of the first retardation layer and the second retardation layer are 1.50 to 1.70, the average refractive index of the second adhesive layer is 1.55 or more, and the difference between the average refractive index of the second adhesive layer and that of the first retardation layer and that of the second retardation layer is less than 0.08, the thickness of the polarizer is 1 μm to 8 μm, and the thickness from the polarizer to the second retardation layer is 35 μm or less. In one embodiment, the first retardation layer and the second retardation layer have an average refractive index of 1.59 to 1.60. In one embodiment, the first retardation layer and the second retardation layer are layers in which a liquid crystal compound is aligned and fixed. [Effects of the Invention]
[0007] According to the present invention, it is possible to provide a polarizing plate with a retardation layer that can suppress unevenness in reflected light and improve visibility. [Brief explanation of the drawings]
[0008] [Figure 1] 1 is a cross-sectional view of a retardation layer-attached polarizing plate according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE INVENTION
[0009] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to these embodiments.
[0010] (Definition of terms and symbols) The definitions of terms and symbols used in this specification are as follows. (1) Refractive index (nx, ny, nz) "nx" is the refractive index in the direction in which the in-plane refractive index is greatest (i.e., the slow axis direction), "ny" is the refractive index in the direction perpendicular to the slow axis in the plane (i.e., the fast axis direction), and "nz" is the refractive index in the thickness direction. (2) In-plane phase difference (Re) "Re(λ)" is the in-plane retardation measured at 23°C with light of wavelength λ nm. Re(λ) is calculated by the formula: Re=(nx-ny)×d, where d (nm) is the thickness of the layer (film). For example, "Re(550)" is the in-plane retardation measured at 23°C with light of wavelength 550 nm. (3) Retardation in the thickness direction (Rth) "Rth(λ)" is the retardation in the thickness direction measured with light of wavelength λ nm at 23°C. For example, "Rth(550)" is the retardation in the thickness direction measured with light of wavelength 550 nm at 23°C. Rth(λ) is calculated by the formula: Rth=(nx-nz)×d, where d (nm) is the thickness of the layer (film).
[0011] A. Polarizing plate with retardation layer 1 is a cross-sectional view of a polarizing plate with a retardation layer according to one embodiment of the present invention. The polarizing plate with a retardation layer 10 includes a polarizer 1, a first retardation layer 2, and a second retardation layer 3 in this order.
[0012] The thickness of each of the first retardation layer 2 and the second retardation layer 3 is 5 μm or less. The first retardation layer 2 typically functions as a λ / 2 plate, and the second retardation layer 3 typically functions as a λ / 4 plate. The first retardation layer 2 has a slow axis. In one embodiment, the angle between the slow axis of the first retardation layer 2 and the absorption axis of the polarizer 1 is, for example, 5° to 25°, preferably 10° to 20°, more preferably 10° to 17°, and even more preferably about 15°. The second retardation layer 3 also has a slow axis. The angle between the slow axis of the second retardation layer 3 and the absorption axis of the polarizer 1 is, for example, 60° to 90°, preferably 65° to 85°, more preferably 70° to 78°, and even more preferably about 75°. The angle formed by the slow axis of the first retardation layer 2 and the slow axis of the second retardation layer 3 is, for example, 50° to 70°, preferably 52° to 65°, more preferably 55° to 65°, and even more preferably about 60°. In another embodiment, the angle between the slow axis of the first retardation layer 2 and the absorption axis of the polarizer 1 is, for example, -5° to -25°, preferably -10° to -20°, more preferably -10° to -17°, and still more preferably about -15°. The second retardation layer 3 also has a slow axis. The angle between the slow axis of the second retardation layer 3 and the absorption axis of the polarizer 1 is, for example, -60° to -90°, preferably -65° to -85°, more preferably -70° to -78°, and still more preferably about -75°. The angle between the slow axis of the first retardation layer 2 and the slow axis of the second retardation layer 3 is, for example, 50° to 70°, preferably 52° to 65°, more preferably 55° to 65°, and still more preferably about 60°. In yet another embodiment, the angle between the slow axis of the first retardation layer 2 and the absorption axis of the polarizer 1 is, for example, 60° to 90°, preferably 65° to 85°, more preferably 70° to 78°, and even more preferably about 75°. The second retardation layer 3 also has a slow axis. The angle between the slow axis of the second retardation layer 3 and the absorption axis of the polarizer 1 is, for example, 5° to 25°, preferably 10° to 20°, more preferably 10° to 17°, and even more preferably about 15°. The angle between the slow axis of the first retardation layer 2 and the slow axis of the second retardation layer 3 is, for example, 50° to 70°, preferably 52° to 65°, more preferably 55° to 65°, and even more preferably about 60°. In yet another embodiment, the angle between the slow axis of the first retardation layer 2 and the absorption axis of the polarizer 1 is, for example, -60° to -90°, preferably -65° to -85°, more preferably -70° to -78°, and even more preferably about -75°. The second retardation layer 3 also has a slow axis. The angle between the slow axis of the second retardation layer 3 and the absorption axis of the polarizer 1 is, for example, -5° to -25°, preferably -10° to -20°, more preferably -10° to -17°, and even more preferably about -15°. The angle between the slow axis of the first retardation layer 2 and the slow axis of the second retardation layer 3 is, for example, 50° to 70°, preferably 52° to 65°, more preferably 55° to 65°, and even more preferably about 60°.
[0013] The polarizer 1 and the first retardation layer 2 are bonded together via a first adhesive layer 4, and the first retardation layer 2 and the second retardation layer 3 are bonded together via a second adhesive layer 5. The thickness of each of the first adhesive layer 4 and the second adhesive layer 5 is typically 6 μm or less. The difference between the average refractive index of the first adhesive layer 4 and the average refractive index of the layers adjacent to the first adhesive layer 4 (the polarizer 1 and the first retardation layer 2) is typically less than 0.12. The difference between the average refractive index of the first adhesive layer 4 and the average refractive index of the adjacent layers is preferably less than 0.10, more preferably less than 0.08, and even more preferably 0.06 or less. The average refractive index of the second adhesive layer 5 is 1.55 or more, and the difference between the average refractive index of the layers adjacent to the second adhesive layer 5 (the first retardation layer 2 and the second retardation layer 3) is less than 0.08. The difference between the average refractive index of the second adhesive layer 5 and the average refractive index of the adjacent layers is preferably 0.06 or less, more preferably 0.01 or less. By using the above-mentioned retardation layer-attached polarizing plate 10 in a display device, it is possible to suppress unevenness in reflected light of the display device and improve visibility. Note that the retardation layer-attached polarizing plate 10 may have a protective film (not shown) on the side of the polarizer 1 opposite to the first retardation layer 2.
[0014] The thickness of the retardation layer-attached polarizing plate 10 (total thickness of polarizer 1 / first adhesive layer 4 / first retardation layer 2 / second adhesive layer 5 / second retardation layer 3) is preferably 4 μm to 35 μm, and more preferably 6 μm to 20 μm.
[0015] B. Polarizer Any appropriate polarizer can be adopted as the polarizer 1. For example, the resin film forming the polarizer may be a single-layer resin film or a laminate of two or more layers.
[0016] Specific examples of polarizers made of a single-layer resin film include hydrophilic polymer films such as polyvinyl alcohol (PVA) films, partially formalized PVA films, and partially saponified ethylene-vinyl acetate copolymer films that have been dyed with iodine or a dichroic substance such as a dichroic dye and stretched, as well as polyene-based oriented films such as dehydrated PVA films and dehydrochlorinated polyvinyl chloride films. Polarizers obtained by dyeing a PVA film with iodine and uniaxially stretching it are preferred because of their excellent optical properties.
[0017] The dyeing with iodine is carried out, for example, by immersing the PVA film in an aqueous iodine solution. The stretching ratio of the uniaxial stretching is preferably 3 to 7 times. The stretching may be carried out after the dyeing treatment or while dyeing. Alternatively, the PVA film may be stretched and then dyed. If necessary, the PVA film may be subjected to a swelling treatment, a crosslinking treatment, a washing treatment, a drying treatment, or the like. For example, by immersing the PVA film in water and washing it before dyeing, it is possible to wash away dirt and antiblocking agents on the surface of the PVA film, and also to swell the PVA film, thereby preventing uneven dyeing.
[0018] Specific examples of polarizers obtained using laminates include a laminate of a resin substrate and a PVA-based resin layer (PVA-based resin film) laminated on the resin substrate, or a polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer coated on the resin substrate. A polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer coated on the resin substrate can be produced, for example, by applying a PVA-based resin solution to the resin substrate and drying the resin substrate to form a PVA-based resin layer on the resin substrate, thereby obtaining a laminate of the resin substrate and the PVA-based resin layer, and then stretching and dyeing the laminate to convert the PVA-based resin layer into a polarizer. In this embodiment, stretching typically involves immersing the laminate in an aqueous boric acid solution and stretching it. Furthermore, stretching can optionally further include in-air stretching the laminate at an elevated temperature (e.g., 95°C or higher) before stretching in the aqueous boric acid solution. The obtained resin substrate / polarizer laminate may be used as is (i.e., the resin substrate may be used as a protective layer for the polarizer), or the resin substrate may be peeled off from the resin substrate / polarizer laminate and any appropriate protective layer depending on the purpose may be laminated on the peeled surface. Details of such a method for producing a polarizer are described, for example, in JP 2012-73580 A. The entire disclosure of this publication is incorporated herein by reference.
[0019] The thickness of the polarizer 1 is preferably 12 μm or less, more preferably 1 μm to 10 μm, still more preferably 3 μm to 8 μm, and particularly preferably 3 μm to 5 μm. When the thickness of the polarizer 1 is within this range, the entire retardation layer-attached polarizing plate 10 can be made thin. The above-mentioned thin polarizer 1 can be produced by using a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate.
[0020] The polarizer 1 preferably exhibits absorption dichroism at any wavelength between 380 nm and 780 nm. The single transmittance of the polarizer is preferably 42.0% to 46.0%, and more preferably 44.5% to 46.0%. The degree of polarization of the polarizer is preferably 97.0% or more, more preferably 99.0% or more, and even more preferably 99.9% or more.
[0021] The average refractive index of the polarizer 1 is preferably 1.48 to 1.65, and typically 1.55. When the average refractive index of the polarizer 1 is within the above range, the difference between the average refractive index of the polarizer 1 and that of the first adhesive layer 4 can be easily adjusted.
[0022] C. First retardation layer and second retardation layer As described above, in one embodiment of the present invention, the first retardation layer 2 can function as a λ / 2 plate, and the second retardation layer 3 can function as a λ / 4 plate. By having the first retardation layer 2 function as a λ / 2 plate, the retardation can be appropriately adjusted with respect to the wavelength dispersion characteristics (particularly, the wavelength range in which the retardation deviates from λ / 4) after lamination with the second retardation layer 3 functioning as a λ / 4 plate, and the circular polarization function can be exhibited over a wide wavelength range.
[0023] The in-plane retardation Re(550) of such a first retardation layer 2 is 180 nm to 320 nm, preferably 200 nm to 300 nm, and more preferably 200 nm to 280 nm. The first retardation layer 2 typically has an index ellipsoid of nx>ny=nz or nz=nx>ny. The in-plane retardation Re(550) of such a second retardation layer 3 is 80 nm to 180 nm, preferably 90 nm to 170 nm, and more preferably 100 nm to 150 nm. The second retardation layer 3 typically has an index ellipsoid of nx>ny=nz or nz=nx>ny.
[0024] The average refractive index of the first retardation layer 2 is preferably 1.50 to 1.70, typically 1.59 or 1.60. When the average refractive index of the first retardation layer 2 is within the above range, the difference between the average refractive index of the first adhesive layer 4 and / or the average refractive index of the second adhesive layer 5 can be less than 0.12 (even 0.06 or less). The thickness of the first retardation layer 2 is preferably 1 μm to 5 μm, more preferably 1 μm to 3 μm, and particularly preferably 2 μm.
[0025] The average refractive index of the second retardation layer 3 is preferably 1.50 to 1.70, and typically 1.59 or 1.60. When the average refractive index of the second retardation layer 3 is within the above range, the difference from the average refractive index of the second adhesive layer 5 can be less than 0.08. The thickness of the second retardation layer 3 is preferably 1 μm to 5 μm, more preferably 1 μm to 3 μm, and particularly preferably 1 μm.
[0026] In one embodiment, the first retardation layer 2 and / or the second retardation layer 3 may be a layer in which a liquid crystal compound is aligned and fixed. By using a liquid crystal compound, the difference between nx and ny of the resulting first retardation layer 2 and / or second retardation layer 3 can be made significantly larger than that of a non-liquid crystal material, and therefore the thickness of the first retardation layer and / or the second retardation layer required to obtain a desired in-plane retardation can be made significantly smaller. As a result, the retardation layer-attached polarizing plate 10 (and ultimately the organic EL display device) can be made even thinner. In this specification, the term "alignment layer" refers to a layer in which a liquid crystal compound is aligned in a predetermined direction within the layer and the alignment state is fixed.
[0027] In one embodiment, typically, rod-shaped liquid crystal compounds are aligned in the slow axis direction of the first retardation layer 2 (second retardation layer 3) (homogeneous alignment). Examples of liquid crystal compounds include liquid crystal compounds whose liquid crystal phase is a nematic phase (nematic liquid crystals). Examples of liquid crystal compounds that can be used include liquid crystal polymers and liquid crystal monomers. The mechanism by which the liquid crystal compound exhibits liquid crystallinity may be either lyotropic or thermotropic. Liquid crystal polymers and liquid crystal monomers may be used alone or in combination. Any appropriate liquid crystal monomer may be used as the liquid crystal monomer. For example, polymerizable mesogenic compounds described in JP-A-2002-533742 (WO 00 / 37585), EP 358208 (US 5,211,877), EP 66137 (US 4,388,453), WO 93 / 22397, EP 0261712, DE 19504224, DE 4408171, and GB 2,280,445 can be used. Specific examples of such polymerizable mesogenic compounds include BASF's LC242 (trade name), Merck's E7 (trade name), and Wacker-Chem's LC-Sillicon-CC3767 (trade name). Preferred liquid crystal monomers include nematic liquid crystal monomers. Specific examples of liquid crystal compounds and details of a method for forming a solidified alignment layer are described in JP-A-2006-163343, the disclosure of which is incorporated herein by reference.
[0028] In another embodiment, typically, the discotic liquid crystal compound is aligned in any one of vertical alignment, hybrid alignment, and tilt alignment. Examples of the liquid crystal compound include discotic liquid crystal compounds. Typically, the discotic liquid crystal compound is aligned such that its discotic plane is substantially perpendicular to the film plane of the first retardation layer (second retardation layer). The discotic liquid crystal compound being substantially perpendicular means that the average angle between the film plane and the discotic plane of the discotic liquid crystal compound is within the range of 70° to 90°. An angle of 80° to 90° is more preferred, and an angle of 85° to 90° is even more preferred. Examples of discotic liquid crystal compounds that can be preferably used include, but are not limited to, those described in JP-A Nos. 2007-108732 and 2010-244038.
[0029] D. First adhesive layer As described above, the difference between the average refractive index of the first adhesive layer 4 and the average refractive index of the layer adjacent to the first adhesive layer 4 is less than 0.12. When a thin retardation layer-attached polarizing plate having a thin retardation layer (for example, 5 μm or less) is used in a display device, the refractive index difference between the layers constituting the retardation layer-attached polarizing plate can cause thickness unevenness, unevenness, etc. of each layer to be visible as interference unevenness. In contrast, by making the difference between the average refractive index of the first adhesive layer 4 and the average refractive index of the layer adjacent to the first adhesive layer 4 less than 0.12, the above-mentioned interference unevenness can be suppressed, and as a result, visibility can be improved.
[0030] The average refractive index of the first adhesive layer 4 is preferably 1.52 to 1.64, more preferably 1.55 to 1.64. The thickness of the first adhesive layer 4 is preferably 10 nm to 6 μm, and further preferably 200 nm to 2 μm.
[0031] The adhesive that can constitute the first adhesive layer 4 preferably has transparency and optical isotropy. A typical example of an adhesive that can be used is an active energy ray-curable adhesive. The active energy ray-curable adhesive can be selected from radical curable, cationic curable, anionic curable, and other types as needed, and it is also possible to use an appropriate combination, such as a hybrid of radical curable and cationic curable types. Examples of radical curable adhesives include adhesives containing, as a curing component, a compound (e.g., a monomer and / or oligomer) having a radically polymerizable group such as a (meth)acrylate group or a (meth)acrylamide group. Note that "(meth)acrylic" refers to acrylic and / or methacrylic.
[0032] By adjusting the type, combination, and compounding ratio of double-bond-containing monomers and / or oligomers and crosslinking agents, etc., active energy ray-curable adhesives with desired properties (e.g., refractive index after curing) can be obtained. Components that can adjust the refractive index after curing include, for example, compounds with aromatic rings, compounds with halogen atoms, compounds with sulfur atoms, and inorganic particles such as titania and zirconia. Examples of compounds with aromatic rings include compounds with a naphthalene skeleton, a phenoxybenzyl skeleton, a fluorene skeleton, and a 9-vinylcarbazole skeleton. Furthermore, the adhesive may contain a compound containing a (meth)acryloyl group as a diluent component, an acrylic oligomer as a plasticizer, and a radical photopolymerization initiator as a photopolymerization initiator.
[0033] E. Second adhesive layer The second adhesive layer 5 may be made of any appropriate adhesive. As described above, the difference between the average refractive index of the second adhesive layer 5 and the average refractive index of the layer adjacent to the second adhesive layer 5 is less than 0.08. This can suppress the above-mentioned interference unevenness, and as a result, can improve visibility.
[0034] The average refractive index of the second adhesive layer 5 is 1.55 or more, preferably 1.55 to 1.64, and more preferably 1.55 to 1.63. The thickness of the second adhesive layer 5 is preferably 10 nm to 6 μm, and further preferably 200 nm to 2 μm. The adhesive that can form the second adhesive layer 5 is the same as the adhesive described for the first adhesive layer 4 in Section D.
[0035] F. Protective film The protective film is formed of any appropriate film that can be used as a protective film for the polarizer 1. Specific examples of materials that serve as the main component of the film include cellulose-based resins such as triacetyl cellulose (TAC), and transparent resins such as polyesters, polyvinyl alcohols, polycarbonates, polyamides, polyimides, polyethersulfones, polysulfones, polystyrenes, polynorbornenes, polyolefins, (meth)acrylics, and acetates. Other examples include thermosetting or ultraviolet-curing resins such as (meth)acrylics, urethanes, (meth)acrylic urethanes, epoxy resins, and silicone resins. Other examples include glassy polymers such as siloxane polymers. Polymer films described in JP 2001-343529 A (WO 01 / 37007) can also be used. Examples of materials that can be used for this film include a resin composition containing a thermoplastic resin having substituted or unsubstituted imide groups in its side chains and a thermoplastic resin having substituted or unsubstituted phenyl and nitrile groups in its side chains, such as a resin composition containing an alternating copolymer of isobutene and N-methylmaleimide and an acrylonitrile-styrene copolymer.The polymer film can be, for example, an extrusion molded product of the above resin composition.
[0036] The (meth)acrylic resin preferably has a Tg (glass transition temperature) of 115°C or higher, more preferably 120°C or higher, even more preferably 125°C or higher, and particularly preferably 130°C or higher, because this can provide excellent durability. The upper limit of the Tg of the (meth)acrylic resin is not particularly limited, but is preferably 170°C or lower from the viewpoint of moldability, etc.
[0037] As the (meth)acrylic resin, any appropriate (meth)acrylic resin can be used as long as it does not impair the effects of the present invention. Examples include poly(meth)acrylic acid esters such as polymethyl methacrylate, methyl methacrylate-(meth)acrylic acid copolymers, methyl methacrylate-(meth)acrylic acid ester copolymers, methyl methacrylate-acrylic acid ester-(meth)acrylic acid copolymers, methyl (meth)acrylate-styrene copolymers (such as MS resins), and polymers having alicyclic hydrocarbon groups (such as methyl methacrylate-cyclohexyl methacrylate copolymers and methyl methacrylate-norbornyl (meth)acrylate copolymers). Preferred are poly(C1-6 alkyl(meth)acrylates) such as polymethyl (meth)acrylate. More preferred are methyl methacrylate resins containing methyl methacrylate as the main component (50 to 100% by weight, preferably 70 to 100% by weight).
[0038] Specific examples of the (meth)acrylic resin include ACRYPET VH and ACRYPET VRL20A manufactured by Mitsubishi Rayon Co., Ltd., (meth)acrylic resins having a ring structure in the molecule described in JP-A-2004-70296, and high-Tg (meth)acrylic resins obtained by intramolecular crosslinking or intramolecular cyclization reaction.
[0039] As the (meth)acrylic resin, a (meth)acrylic resin having a lactone ring structure is particularly preferred in terms of high heat resistance, high transparency, and high mechanical strength. Examples of the (meth)acrylic resin having a lactone ring structure include (meth)acrylic resins having a lactone ring structure described in JP-A No. 2000-230016, JP-A No. 2001-151814, JP-A No. 2002-120326, JP-A No. 2002-254544, JP-A No. 2005-146084, etc.
[0040] The (meth)acrylic resin having a lactone ring structure has a mass average molecular weight (sometimes referred to as weight average molecular weight) of preferably 1,000 to 2,000,000, more preferably 5,000 to 1,000,000, still more preferably 10,000 to 500,000, and particularly preferably 50,000 to 500,000.
[0041] The (meth)acrylic resin having a lactone ring structure preferably has a Tg (glass transition temperature) of 115°C or higher, more preferably 125°C or higher, even more preferably 130°C or higher, particularly preferably 135°C or higher, and most preferably 140°C or higher. This is because excellent durability can be obtained. The upper limit of the Tg of the (meth)acrylic resin having a lactone ring structure is not particularly limited, but from the viewpoint of moldability, etc., it is preferably 170°C or lower. In this specification, "(meth)acrylic" refers to acrylic and / or methacrylic.
[0042] The retardation layer-attached polarizing plate 10 of the present invention is typically placed on the viewing side of an image display device, and the protective film is typically placed on the viewing side. Therefore, the protective film may be subjected to surface treatment such as hard coating treatment, anti-reflection treatment, anti-sticking treatment, anti-glare treatment, etc., as necessary.
[0043] The thickness of the protective film may be any appropriate thickness as long as the effects of the present invention are obtained. The thickness of the protective film is, for example, 10 μm to 100 μm, and preferably 12 μm to 90 μm. If a surface treatment is applied, the thickness of the protective film includes the thickness of the surface treatment layer.
[0044] G.Display device The retardation layer-attached polarizing plate described in the above items A to F can be applied to display devices such as liquid crystal display devices and organic EL display devices. Therefore, the present invention encompasses display devices using the above retardation layer-attached polarizing plate. A display device according to an embodiment of the present invention includes a display element and the retardation layer-attached polarizing plate described in the above items A to F, which is arranged on the viewing side of the display element. The retardation layer-attached polarizing plate is arranged so that the second retardation layer 3 faces the display element. [Example]
[0045] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. The methods for measuring each property are as follows. 1. Refractive index measurement of polarizers Using a prism coupler SPA-4000 (manufactured by Cylon Technology), the in-plane refractive index of the polarizer was measured in the direction perpendicular to the absorption axis, the direction of the absorption axis, and the thickness direction, and the average value was taken as the average refractive index of the polarizer. The measurement temperature was 23°C and the measurement wavelength was 532 nm. 2. Refractive index measurement of the retardation layer Using a prism coupler SPA-4000 (manufactured by Cylon Technology), the in-plane refractive index of the retardation film was measured in the direction perpendicular to the slow axis, the direction of the slow axis, and the thickness direction, and the average value was taken as the average refractive index of the retardation layer. The measurement temperature was 23°C and the measurement wavelength was 532 nm. 3. Refractive index measurement of adhesive layer Using a prism coupler SPA-4000 (manufactured by Cylon Technology), the in-plane refractive index and the refractive index in the thickness direction of the cured adhesive that constitutes the adhesive layer were measured, and the average value was taken as the average refractive index of the adhesive layer. The measurement temperature was 23°C and the measurement wavelength was 532 nm. 4. Retardation measurement of the retardation layer Measurement was performed using an Axoscan (manufactured by Axometrics) at a measurement temperature of 23°C and a measurement wavelength of 550 nm.
[0046] (Fabrication of polarizer) An amorphous polyethylene terephthalate (A-PET) film (manufactured by Mitsubishi Plastics, Inc., product name "Novaclear," thickness: 100 μm) was used as the resin substrate. An aqueous solution of polyvinyl alcohol (PVA) resin (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., product name "GOHSENOL (registered trademark) NH-26") was applied to one side of the resin substrate at 60°C and dried to form a 7 μm-thick PVA-based resin layer. The laminate thus obtained was immersed for 30 seconds in an insolubilization bath (a boric acid aqueous solution obtained by blending 4 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 30°C (insolubilization step). It was then immersed for 60 seconds in a dye bath (an iodine aqueous solution obtained by blending 0.2 parts by weight of iodine and 2 parts by weight of potassium iodide with 100 parts by weight of water) at a liquid temperature of 30°C (dyeing step). Next, the laminate was immersed in a crosslinking bath (a boric acid aqueous solution obtained by blending 3 parts by weight of potassium iodide and 3 parts by weight of boric acid per 100 parts by weight of water) at a liquid temperature of 30°C for 30 seconds (crosslinking step). Thereafter, the laminate was immersed in a boric acid aqueous solution (a solution obtained by blending 4 parts by weight of boric acid and 5 parts by weight of potassium iodide per 100 parts by weight of water) at a liquid temperature of 60°C, while being uniaxially stretched in the longitudinal direction (machine direction) between rolls operating at different peripheral speeds (step B). The immersion time in the boric acid aqueous solution was 120 seconds, and the laminate was stretched until just before breaking. The laminate was then immersed in a washing bath (a solution obtained by blending 3 parts by weight of potassium iodide per 100 parts by weight of water) and then dried with hot air at 60°C (washing and drying step). In this way, a laminate was obtained in which a 5 μm-thick polarizer was formed on a resin substrate. Next, the resin substrate was peeled off from the polarizer, and a protective film (acrylic transparent protective film described in JP 2012-3269 A) was attached to one surface of the polarizer to obtain a polarizer with a protective film. The above polarizer with a protective film was subjected to a corona treatment before use.
[0047] (Preparation of Retardation Film Constituting Retardation Layer) (Retardation film A) A 2-μm-thick retardation film A was fabricated on a transparent resin substrate with a rubbed λ / 2 alignment film. The coating solution contained a rod-shaped, polymerizable nematic liquid crystal monomer and was solidified while maintaining the refractive index anisotropy. The in-plane refractive index of the retardation film A was 1.55 in the fast axis direction, 1.68 in the slow axis direction, and 1.55 in the thickness direction, with an average refractive index of 1.59. The in-plane retardation Re(550) of the retardation film A was 260 nm. The resulting retardation film was subjected to corona treatment before use. (Retardation film B) A coating solution containing a rod-shaped, polymerizable nematic liquid crystal monomer was applied to a λ / 4 alignment transparent resin substrate with a rubbed alignment film, and solidified while maintaining the refractive index anisotropy, to produce a 1 μm-thick retardation film A on the transparent resin substrate. The in-plane refractive index of retardation film B was 1.55 in the fast axis direction, 1.68 in the slow axis direction, and 1.55 in the thickness direction, with an average refractive index of 1.59. The in-plane retardation Re(550) of retardation film B was 120 nm. The obtained retardation film was subjected to corona treatment before use. (Retardation film C) A transparent resin substrate made of cellulose acylate was subjected to alkaline saponification treatment. An alignment film coating solution was then applied to the alkaline saponification-treated surface of the cellulose acylate and dried to perform a λ / 2 alignment treatment. A coating solution containing a discotic liquid crystal compound was then applied to the alignment-treated surface of the transparent support, and the alignment of the liquid crystal compound was fixed by heating and UV irradiation, thereby producing a 2 μm-thick retardation film C on the transparent resin substrate. The in-plane refractive index of the retardation film C was 1.53 in the fast axis direction, 1.64 in the slow axis direction, and 1.64 in the thickness direction, with an average refractive index of 1.60. The in-plane retardation Re(550) of the retardation film C was 246 nm. The obtained retardation film was subjected to corona treatment before use. (Retardation film D) A transparent resin substrate made of cellulose acylate was subjected to alkaline saponification treatment. An alignment film coating solution was then applied to the alkaline saponification-treated surface of the cellulose acylate and dried to perform a λ / 4 alignment treatment. A coating solution containing a discotic liquid crystal compound was then applied to the alignment-treated surface of the transparent support, and the alignment of the liquid crystal compound was fixed by heating and UV irradiation, thereby producing a 1 μm-thick retardation film D on the transparent resin substrate. The in-plane refractive index of retardation film D was 1.53 in the fast axis direction, 1.64 in the slow axis direction, and 1.64 in the thickness direction, with an average refractive index of 1.60. The in-plane retardation Re(550) of retardation film D was 123 nm. The resulting retardation film was subjected to corona treatment before use.
[0048] (Preparation of adhesive that constitutes adhesive layer) (Adhesive A) Adhesive A was prepared by mixing 50 parts of Plaxel FA1DDM (manufactured by Daicel Corporation), 40 parts of acryloylmorpholine (ACMO: registered trademark) (manufactured by Kojinsha), 10 parts of ARFON UP-1190 (manufactured by Toagosei Co., Ltd.), 3 parts of a photopolymerization initiator (product name "KAYACURE DETX-S", manufactured by Nippon Kayaku Co., Ltd.), and 3 parts of IRGACURE 907 (manufactured by BASF Japan Ltd.). The resulting adhesive A was photocured (300 mJ / cm 2 The cured product obtained by the above procedure had an in-plane refractive index of 1.52, a refractive index in the thickness direction of 1.52, and an average refractive index of these of 1.52. (Adhesive B) Adhesive B was prepared by mixing 40 parts of Light Acrylate POB-A (Kyoeisha Chemical Co., Ltd.), 10 parts of Placcel FA1DDM (Daicel Corporation), 40 parts of Acryloylmorpholine (ACMO: registered trademark) (Kojinsha Co., Ltd.), 10 parts of ARFON UP-1190 (Toagosei Co., Ltd.), 3 parts of a photopolymerization initiator (product name "KAYACURE DETX-S", Nippon Kayaku Co., Ltd.), and 3 parts of IRGACURE 907 (BASF Japan Ltd.). The resulting adhesive B was photocured (300 mJ / cm 2 The cured product obtained by the above procedure had an in-plane refractive index of 1.55, a refractive index in the thickness direction of 1.55, and an average refractive index of these of 1.55. (Adhesive C) Adhesive C was prepared by mixing 70 parts of Oxol EA-F5710 (Osaka Gas Chemicals Co., Ltd.), 10 parts of Plaxel FA1DDM (Daicel Corporation), 18 parts of acryloylmorpholine (ACMO: registered trademark) (Kojinsha Co., Ltd.), 5 parts of ARFON UP-1190 (Toagosei Co., Ltd.), and 3 parts of a photopolymerization initiator (product name "DAROCUR1173", BASF Japan Ltd.). The resulting adhesive C was photocured (300 mJ / cm 2 The cured product obtained by the above procedure had an in-plane refractive index of 1.60, a refractive index in the thickness direction of 1.60, and an average refractive index of these of 1.60. (Adhesive D) Adhesive D was prepared by mixing 35 parts of 9-vinylcarbazole (manufactured by Tokyo Chemical Industry Co., Ltd.), 40 parts of Oxol EA-F5710 (manufactured by Osaka Gas Chemicals Co., Ltd.), 20 parts of acryloylmorpholine (ACMO: registered trademark), 5 parts of ARFON UP-1190 (manufactured by Toagosei Co., Ltd.), and 3 parts of a photopolymerization initiator (product name "DAROCUR1173", manufactured by BASF Japan Ltd.). The resulting adhesive D was photocured (300 mJ / cm 2 The cured product obtained by the above procedure had an in-plane refractive index of 1.64, a refractive index in the thickness direction of 1.64, and an average refractive index of these of 1.64.
[0049] Example 1 Adhesive A constituting the first adhesive layer was applied to the polarizer, and retardation film A constituting the first retardation layer was transferred from the transparent resin substrate to the adhesive A-coated surface so that the angle between the absorption axis of the polarizer and the slow axis of the retardation film A was 15°. Then, the film was irradiated with UV (300 mJ / cm 2 ) to cure the adhesive A. Next, adhesive B constituting a second adhesive layer was applied to the surface of retardation film A opposite to the polarizer, and retardation film D constituting a second retardation layer was transferred from the transparent resin substrate to the adhesive B-coated surface so that the angle between the absorption axis of the polarizer and the slow axis of retardation film D was 75° and the angle between the slow axis of retardation film A and the slow axis of retardation film D was 60°. Then, the adhesive B was irradiated with UV (300 mJ / cm 2) and curing adhesive B to obtain a polarizing plate with a retardation layer. The thickness of the cured adhesive A (first adhesive layer) was 1 μm, and the thickness of the cured adhesive B (second adhesive layer) was 1 μm.
[0050] <Example 2> A polarizing plate with a retardation layer was produced in the same manner as in Example 1, except that adhesive B was used as the adhesive constituting the first adhesive layer.
[0051] Example 3 A polarizing plate with a retardation layer was produced in the same manner as in Example 2, except that adhesive C was used as the adhesive constituting the second adhesive layer.
[0052] Example 4 A polarizing plate with a retardation layer was produced in the same manner as in Example 1, except that adhesive C was used as the adhesive constituting the first adhesive layer and adhesive D was used as the adhesive constituting the second adhesive layer.
[0053] <Example 5> Adhesive B constituting the first adhesive layer was applied to the polarizer, and retardation film C constituting the first retardation layer was transferred from the transparent resin substrate to the adhesive B-coated surface so that the angle between the absorption axis of the polarizer and the slow axis of the retardation film C was 75°. Then, UV irradiation (300 mJ / cm 2 ) to cure the adhesive B. Next, the adhesive B constituting the second adhesive layer was coated on the surface of the retardation film C opposite the polarizer, and the retardation film B constituting the second retardation layer was transferred from the transparent resin substrate to the adhesive B-coated surface so that the angle between the absorption axis of the polarizer and the slow axis of the retardation film B was 15° and the angle between the slow axis of the retardation film C and the slow axis of the retardation film B was 60°. 2 ) and curing adhesive B to obtain a polarizing plate with a retardation layer. The thickness of the cured adhesive B (first adhesive layer) was 1 μm, and the thickness of the cured adhesive B (second adhesive layer) was 1 μm.
[0054] Example 6 A polarizing plate with a retardation layer was produced in the same manner as in Example 2, except that retardation film C was used as the retardation film constituting the first retardation layer and retardation film D was used as the retardation film constituting the second retardation layer.
[0055] Example 7 A polarizing plate with a retardation layer was produced in the same manner as in Example 2, except that the retardation film B was used as the retardation film constituting the second retardation layer.
[0056] <Comparative Example 1> A polarizing plate with a retardation layer was produced in the same manner as in Example 1, except that adhesive A was used as the adhesive constituting the second adhesive layer.
[0057] <Comparative Example 2> A polarizing plate was produced in the same manner as in Comparative Example 1, except that adhesive B was used as the adhesive constituting the first adhesive layer.
[0058] (evaluation) The polarizing plates with a retardation layer of each of the Examples and Comparative Examples were attached to a reflector via an acrylic adhesive, and the appearance was visually observed under a three-wavelength tube. The results were evaluated according to the following criteria and are shown in Table 1. No visible unevenness was observed... Virtually no visible unevenness (no problems in actual use) Unevenness was visible... × [Table 1] [Industrial Applicability]
[0059] The retardation layer-attached polarizing plate of the present invention is preferably used in, for example, image display devices, specifically, as a liquid crystal panel for liquid crystal televisions, liquid crystal displays, mobile phones, digital cameras, video cameras, portable game consoles, car navigation systems, copiers, printers, fax machines, clocks, microwave ovens, etc., and as an antireflection plate for organic EL devices. [Explanation of symbols]
[0060] 1 polarized photon 2 1st phase difference layer 3. Second phase difference layer 4 1st layer 5 Second layer 10-phase phase difference polarizing plate
Claims
1. A polarizer, a first retardation layer, and a second retardation layer in this order, the polarizer and the first retardation layer are bonded to each other via a first adhesive layer, The first retardation layer and the second retardation layer are bonded to each other via a second adhesive layer, The first retardation layer and the second retardation layer have a thickness of 5 μm or less, the first retardation layer and the second retardation layer have an average refractive index of 1.50 to 1.70; The average refractive index of the second adhesive layer is 1.55 or more, and the absolute value of the difference between the average refractive index of the second adhesive layer and the average refractive index of the first retardation layer and the absolute value of the difference between the average refractive index of the second retardation layer and the average refractive index of the second retardation layer are 0.01 or less, The thickness of the polarizer is 1 μm to 8 μm, The thickness from the polarizer to the second retardation layer is 35 μm or less. Polarizing plate with retardation layer.
2. 2. The polarizing plate with a retardation layer according to claim 1, wherein the average refractive index of the first retardation layer and the second retardation layer is 1.59 to 1.
60.
3. 3. The polarizing plate with a retardation layer according to claim 1, wherein the first retardation layer and the second retardation layer are layers in which a liquid crystal compound is aligned and fixed.
Citation Information
Patent Citations
Laminated wavelength plate, circularly polarized light plate and liquid crystal display device
JP1999149015A
Polarizing element
JP2003307622A
Polarizing film, elliptically polarizing film, circularly polarizing film, and liquid crystal display device
JP2004233872A
Liquid crystalline di(METH)acrylate compound, and retardation film, optical film, polarizing plate and liquid crystal panel obtained using the same, and liquid crystal display device
JP2006056822A
Retardation film, polarizing plate, liquid crystal panel, liquid crystal display device, and method for manufacturing retardation film
JP2006098460A